Analysis of X‐band PolInSAR coherence characteristics in forested areas. Issue 6 (2nd May 2017) - Zhang, Hai‐ying; Li, Zhen‐fang; Wang, Zhi‐bin; Fang, Chao
Abstract : The X‐band coherence statistical characteristics related to the height of ambiguity, polarisation and resolution in two typical forested areas are investigated, using X‐band multi‐baseline polarimetric synthetic aperture radar interferometry (PolInSAR) data acquired by an automobile‐based interferometric synthetic aperture radar (InSAR) system. The influences of the polarisation and resolution on coherence are carefully analysed. The results show that the volume decorrelation in forested areas is independent of the polarisation and the coherence decreases with the reduction of the resolution. In addition, an empirical coherence model in relation to the height of ambiguity, resolution, forest height and range slope is proposed, according to the coherence statistical characteristics of the experimental data. The model can be used to calculate the mean coherence of forested areas under a specific system baseline and therefore it can play an important role in X‐band InSAR baseline configuration for forest mapping.